2006
DOI: 10.1080/14992020600876519
|View full text |Cite
|
Sign up to set email alerts
|

Spatial audio through a bone conduction interface

Abstract: Headphones are the standard presentation device for radio communication in the military. Although bone conduction devices possess several advantages over headphones for some military applications, they are generally considered inappropriate for inclusion in a multi-channel system. The current study tested the feasibility of a multi-channel bone conduction system by measuring the localizability of spatialized auditory stimuli presented through a pair of bone conduction vibrators. Listeners localized a Gaussian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 18 publications
(18 reference statements)
1
42
0
Order By: Relevance
“…In this study, we opted to use captured spatial audio rather than use HRTFs. While we feel that captured audio should be used for RW sounds, in order to leverage the quality of the sample, we also feel that HRTFs should be used for CG sound, as others have found that localization performance using HRTFs to be indistinguishable comparing headphones to BCH devices [9]. Another conclusion has to do with the frequency response of the BCH unit used in our study.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In this study, we opted to use captured spatial audio rather than use HRTFs. While we feel that captured audio should be used for RW sounds, in order to leverage the quality of the sample, we also feel that HRTFs should be used for CG sound, as others have found that localization performance using HRTFs to be indistinguishable comparing headphones to BCH devices [9]. Another conclusion has to do with the frequency response of the BCH unit used in our study.…”
Section: Discussionmentioning
confidence: 81%
“…This occurs because vibrations from the transducer on one side of the head not only reach the near cochlea, but also the cochlea of the far ear. However, MacDonald et al (2006) showed that the interaural level difference and the interaural time delay of signals displayed using bone conduction are sufficient for users to achieve localization performance similar to standard headphones [9]. The study by MacDonald et al used individualized HRTFs for spatialized headphone and bone-conduction audio, and measured how well four listeners could judge the source of a sound played at one of eight locations equally spaced around the listener in the horizontal plane of the head.…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Until recently, TC conveyed audio signal but not spatial information, and so the experience was not equivalent (in this respect) to real-world hearing. Latterly, researchers have shown that a considerable of degree of lateralisation, in some case approaching that of normal binaural hearing, is feasible [10][11][12]. Nevertheless, the results lack equivalence in terms of overall spatial performance, significantly lacking spatial attributes such as externalisation, spaciousness, range perception and elevation perception.…”
Section: Tissue Conduction Of Soundmentioning
confidence: 99%